Impact of diabetes on clinical outcome in severely burned patients. Issue 1 (February 2023) - Aschacher, Olivia; Kaider, Alexandra; Sternat, Nikolaus; Ederer, Ines Ana; Stievano, Simona; Radtke, Christine; Hacker, Stefan; Pauzenberger, Reinhard
Highlights: Risk factors for mortality of diabetic burned patients were age, female, full thickness burns, %TBSA and inhalation injury. Diabetic patients with a TBSA of 30–39% had a survival rate of 50%, while 40% or more had a mortality rate of 50–100%. Diabetic patients had a higher odds ratio for mortality after adjustment for %TBSA. Abstract: Introduction: According to the International Diabetes Federation, approximately 425 million people worldwide suffer from diabetes mellitus, a figure that will double in the next 20 years. Data on the ratio of treated diabetics in burn intensive care units remain scarce and the effects on the mortality rate are poorly defined. Methods: Our retrospective, single-centre study aimed to evaluate differences in the risk factors due to diabetes mellitus, the clinical outcome and the patient population of diabetic patients after severe burn injuries over a time period of 21 years. Results: Despite increasing numbers of diabetic patients, the ratio of burn patients suffering from diabetes remained stable during the study period. The risk factors for mortality were higher age (OR 1.03, 95% confidence interval (CI), 1.02–1.04, p < 0.0001), female sex (OR 1.56, 95% CI, 1.06–2.29, p = 0.025), higher % total body surface area (TBSA) (OR 3.88, 95% CI, 2.81–5.46, p < 0.0001), full thickness burns (OR 8.58, 95% CI, 3.84 – 23.60, p < 0.0001) and the presence of inhalation injuries (OR 4.68, 95% CI, 3.15–7.02, p < 0.0001) Patients with diabetes had a smaller extent of burned areas with a median TBSA of 30% (quartiles: 22–50%, p = 0.036) compared to non-diabetic patients (35% (25–55%)) but had a similar length of stay with a median of 29 (quartiles: 13–44) days vs. 23 (10–48) days. Outcome analysis showed an overall mortality of 35.6%. Diabetes was not associated with higher mortality rate after burn injury in a univariate model (OR 1.80, 95% CI 0.92–3.51). After correction for %TBSA, the effect of diabetes on mortality was significant (OR 2.80, 95% CI, 1.33–5.90). Conclusion: Our data indicate higher mortality rates (50–100%) of diabetic patients with TBSA greater than 40% in severely burned patients compared to non-diabetic patients without a significant outcome due to the low number of cases in the subgroup analyses.